2018
DOI: 10.1080/15384101.2017.1361066
|View full text |Cite
|
Sign up to set email alerts
|

Function of RAD6B and RNF8 in spermatogenesis

Abstract: Histone ubiquitination regulates sperm formation and is important for nucleosome removal during spermatogenesis. RNF8 is an E3 ubiquitin ligase, and RAD6B is an E2 ubiquitin-conjugating enzyme. Both proteins participate in DNA damage repair processes via histone ubiquitination. Loss of RNF8 or RAD6B can lead to sterility in male mice. However, the specific mechanisms regulating these ubiquitin-mediated processes are unclear. In this study, we found that RNF8 knockout mice were either subfertile or sterile base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
(91 reference statements)
3
16
0
Order By: Relevance
“…On the other hand, Rnf8-KO mice in our colony did not show abrogation of spermiogenic progression in Rnf8-KO testes, enabling us to confirm that RNF8 is not required for histone-to-protamine exchange. Curiously, the same Rnf8-KO mice were reported to be subfertile in another study (Guo et al, 2018). While that study claimed that RNF8 is required for histone-protamine exchange, fertile Rnf8-KO sperm must have underwent normal histone-protamine exchange to enable fertilization, supporting our conclusion that RNF8 is not required for the histone-to-protamine exchange.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…On the other hand, Rnf8-KO mice in our colony did not show abrogation of spermiogenic progression in Rnf8-KO testes, enabling us to confirm that RNF8 is not required for histone-to-protamine exchange. Curiously, the same Rnf8-KO mice were reported to be subfertile in another study (Guo et al, 2018). While that study claimed that RNF8 is required for histone-protamine exchange, fertile Rnf8-KO sperm must have underwent normal histone-protamine exchange to enable fertilization, supporting our conclusion that RNF8 is not required for the histone-to-protamine exchange.…”
Section: Resultssupporting
confidence: 73%
“…This same line of Rnf8-KO mice was widely used in previous studies of the function of RNF8 in spermatogenesis (Adams et al, 2018;Guo et al, 2018;Hasegawa et al, 2015;Ichijima et al, 2011;Lu et al, 2010;Lu et al, 2013;Santos et al, 2010;Sin et al, 2012;Sin et al, 2015), including the initial study by Lu et al (2010) which suggested a requirement for RNF8 in mediating histone-to-protamine exchange.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the germ cell reproductive process, epigenetic chromatin modifications such as methylation, acetylation and ubiquitination play major roles (Gannon et al, 2014). (Guo et al, 2018;Simhadri et al, 2014;Sun et al, 2016;Ward et al, 2003).…”
Section: Discussionmentioning
confidence: 99%